2018
DOI: 10.3892/or.2018.6302
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑448 inhibits the progression of retinoblastoma by directly targeting ROCK1 and regulating PI3K/AKT signalling pathway

Abstract: Retinoblastoma (RB) is the most common primary intraocular malignancy during infancy and childhood worldwide. Numerous microRNAs (miRNAs) contribute to RB initiation and progression through the regulation of cell proliferation, cycle, apoptosis, migration, invasion and metastasis. Therefore, further investigation concerning the expression, roles and associated mechanisms of RB‑related miRNAs may be beneficial to develop novel strategies for patients with this malignancy. Recently, miRNA‑448 (miR‑448) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…In addition, miR-135a is abnormally down-regulated in gastric cancer, glioma, endometrial cancer and other tumors, while ROCK1 is also abnormally over-expressed in osteosarcoma, hepatocellular carcinoma, retinoblastoma and other cancers. Reverse regulation of the miR-135a and ROCK1 expressions has anti-cancer effects to varying degrees [22][23][24][25][26][27]. Further analysis of the ability of miR-135a and ROCK1 to differentiate NSCLC revealed that the AUC of both in the diagnosis of NSCLC was no less than 0.85, suggesting that both had a high value in screening NSCLC and might serve as biomarkers for the early diagnosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-135a is abnormally down-regulated in gastric cancer, glioma, endometrial cancer and other tumors, while ROCK1 is also abnormally over-expressed in osteosarcoma, hepatocellular carcinoma, retinoblastoma and other cancers. Reverse regulation of the miR-135a and ROCK1 expressions has anti-cancer effects to varying degrees [22][23][24][25][26][27]. Further analysis of the ability of miR-135a and ROCK1 to differentiate NSCLC revealed that the AUC of both in the diagnosis of NSCLC was no less than 0.85, suggesting that both had a high value in screening NSCLC and might serve as biomarkers for the early diagnosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As the first encouraging result, we verified that DANCR did promote osteosarcoma cells’ proliferation and metastasis via up-regulation of ROCK1. According to the previous researches, ROCK1 could be targeted by many miRNAs [ 41 44 ]. Also, it is well known that lncRNA can regulate numbers of miRNAs at the same time, and one miRNA can regulate an army of downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of miRNAs are located at cancer-related genomic regions or fragile sites, indicating that miRNAs may be closely related to cancer initiation and progression (10). Numerous miRNAs are deregulated in RB, such as miR-138 (11), miR-448 (12), miR-498 (13) and miR-613 (14). miRNAs deregulation plays critical roles in RB oncogenesis and development by regulating cell proliferation, apoptosis, cycle, metastasis and invasion (15,16).…”
Section: Introductionmentioning
confidence: 99%